Translanguaging in Multilingual Classrooms: A Perspective From EFL Setting - Wonggo, Mutiara Auralia; Tanipu, Zulkifli; Ali, Sri Widyarti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study investigates the pedagogical role of translanguaging in multilingual English as a Foreign Language (EFL) classrooms, centering on the perspectives of both students and lecturers, along with the underlying factors that inform these views. Adopting a phenomenological approach, the research draws on data from semi-structured interviews, preceded by classroom observations that served to contextualize the phenomenon and refine participant selection. The findings suggest that translanguaging facilitates deeper comprehension, stimulates active learner engagement, and reinforces linguistic confidence. Nonetheless, Its enactment is mediated by institutional norms, asymmetrical language practices, and a general lack of pedagogical awareness. Participants’ perspectives are further influenced by variables such as linguistic background, language engagement, academic expectations and goals, classroom environment and lecturer practices, peer influence and collaborative dynamics, teaching experience and curriculum policy. These insights point to the pressing need for a coherent and principled framework that integrates translanguaging as a deliberate instructional resource rather than an incidental coping mechanism. The study contributes to the evolving discourse on multilingual education and offers implications for enhancing EFL pedagogy in higher education contexts.